Novel ALK gene mutation in inflammatory myofibroblastic tumor of the thyroid: a case report - Yang Guangxu; Li Yao; Xie Jing; Liu Hongsheng (Frontiers in Oncology)
BackgroundInflammatory myofibroblastic tumor (IMT) is a rare soft tissue neoplasm, exceptionally uncommon in the thyroid. Approximately 50%–70% of IMT cases exhibit ALK gene rearrangements or fusions, while ALK point mutations are rare. We report a novel ALK gene mutation, ALK-R395H, in a case of thyroid IMT and review the relevant literature.Case reportA 43-year-old female patient presented with a thyroid mass discovered two months prior. Ultrasound revealed a solid hypoechoic mass in the middle of the left thyroid lobe. Histopathology showed characteristic spindle cell proliferation with plasma cell and lymphocyte infiltration. Immunohistochemistry demonstrated strong expression of Vimentin and ALK-1 in spindle cells, focal SMA expression, and strong positivity for Galectin-3, PAX-8, and TTF-1. Next-generation sequencing identified mutations in NTRK1, GNAS, RB1, and ALK, with a G1184A mutation in ALK exon 5, resulting in a missense mutation ALK(p.R395H) in the extracellular domain, the function of which remains to be elucidated. The pathological diagnosis was thyroid IMT; however, strong expression of thyroid epithelial markers and the ALK mutation suggested possible thyroid carcinoma components or malignant potential. The patient underwent left thyroid lobectomy with isthmus resection, received no adjuvant therapy, and showed no recurrence after 37 months of follow-up.ConclusionThis case reports the discovery of the ALK-R395H mutation in thyroid IMT, providing new insights into its molecular characteristics.